Justicia, cuidado y el planteamiento de una moral comunitaria - Frisancho, Susana (1998)
Kohlberg's theory of moral development is the most accurate approach, within psychology, to the concept of a communitarian morality, essentially with the Just Community approach to moral education. This article, however, asks about the coherence of this approach within the liberal deontological framework of the Kohlbergian theory. The article reviews the concept of community hold by Kohlberg's theory and the caring perspective, theories that eventhough assume different philosophical premises and a different concept of community, call for a communitarian ethics for the development of a real moral self.